Preparation and application of diatomite-paraffin phase change material

By modifying diatomaceous earth and paraffin, and combining vacuum and water bath heating treatment, diatomaceous earth-paraffin phase change materials are prepared, which solves the problem of insufficient optimization of material application parameters in the prior art, and improves the performance of phase change coatings and phase change heat storage mortars.

CN119955481APending Publication Date: 2025-05-09XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510163719.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

In the preparation of diatomaceous earth and paraffin composite phase change materials, the parameter optimization of the specific application of the material is not possible, resulting in poor results in actual applications.

Method used

The diatomaceous earth-paraffin phase change material was prepared by diatomaceous earth modification treatment, paraffin modification treatment, mixed vacuum treatment, water bath heating treatment and cooling and drying treatment, and applied to the preparation of phase change coatings and phase change heat storage mortars.

Benefits of technology

The effective preparation and application of diatomaceous earth-paraffin phase change materials is realized, and the construction property, surface drying time, alkali resistance and scrubbing resistance of phase change coatings are improved, as well as the flow, compressive strength and bonding strength of phase change heat storage mortar.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119955481A_ABST
    Figure CN119955481A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of a diatomite-paraffin phase change material. The preparation comprises diatomite modification treatment, paraffin modification treatment, mixed vacuum treatment, water bath heating treatment and cooling and drying treatment. The method is reasonable in step design and easy and convenient to operate, diatomite and paraffin are modified, pores are prevented from being blocked by impurities and organic matter, subsequent material preparation is facilitated, through vacuum treatment and water bath heating, it is guaranteed that phase-change materials can be effectively mixed and correspondingly stirred during heating, and it is guaranteed that the materials are evenly mixed and fully react; the material preparation effect is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phase change material preparation, and in particular to the preparation and application of a diatomaceous earth-paraffin phase change material. Background Art

[0002] The use of latent heat of phase change materials to store or release thermal energy is suitable for the use of solar energy, waste heat recovery, intelligent automatic air-conditioning buildings, glass greenhouses, phase change thermal storage air conditioners, thermal insulation polymer materials and special fields, and the scope of application is gradually expanding. The thermal performance of building envelopes is closely related to the indoor thermal environment. Improving thermal performance can reduce the energy consumption of building operations. Introducing phase change materials into building envelopes as a new building energy-saving technology can effectively regulate indoor temperature and reduce building energy consumption.

[0003] Those skilled in the art have conducted research on this, such as the preparation method of a diatomite and paraffin composite phase change material proposed in application No. 201410417511.3, which does not require container packaging and can be used directly, has a simple preparation process, low cost, energy saving and environmental protection, and the solvent can be recycled. However, the research on this technical solution is limited to the preparation and synthesis method of the phase change composite material, performance evaluation, etc., and does not optimize the parameters of the specific application of the material. To this end, we propose a preparation and application of a diatomite-paraffin phase change material. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a diatomaceous earth-paraffin phase change material to overcome the technical problems existing in the prior art.

[0005] In order to achieve the above technical objectives and the above technical effects, the present invention provides the following technical solutions: A method for preparing a diatomaceous earth-paraffin phase change material comprises the following steps: S1, diatomite modification treatment, a. Place the original diatomite in a high-temperature box-type electric furnace for calcination. b. Weigh a certain amount of calcined modified diatomite and inject it into a container, and immerse it in a hydrochloric acid solution at a liquid-to-solid ratio of 4:1. c. Heat the container in a water bath at 50°C for 4 hours. d. Washing, filtering and drying the diatomaceous earth after acid washing; S2, paraffin modification treatment, a. Break long-chain paraffin molecules into shorter chains through cleavage reactions. b. further separating and purifying the pyrolysis products to obtain modified paraffin; S3, mixed vacuum treatment, Weigh a certain proportion of modified diatomaceous earth and modified paraffin, mix them and put them into a suction flask, connect it to a circulating water vacuum pump, turn on the switch and pump the suction flask to a certain vacuum degree; S4, water bath heating treatment, Heat the filtration bottle in a water bath at 75°C for 2 hours; S5, cooling and drying treatment, The diatomaceous earth fully adsorbed with paraffin was taken out, cooled to room temperature, and placed for 24 hours to dry, thereby obtaining a diatomaceous earth-paraffin phase change material.

[0006] Preferably, in a method for preparing a diatomaceous earth-paraffin phase change material, the calcination temperature of the high-temperature box-type electric furnace in step 1 is 450° C. and the calcination time lasts for 2 hours.

[0007] Preferably, in a method for preparing a diatomaceous earth-paraffin phase change material, the concentration of the hydrochloric acid solution in step 1 is 5 mol / L.

[0008] Preferably, in a method for preparing a diatomaceous earth-paraffin phase change material, in step 2, deoiled refined wax is used as a raw material to carry out a cracking reaction in a tubular cracking furnace.

[0009] Preferably, in a method for preparing a diatomaceous earth-paraffin phase change material, stirring is performed during water bath heating in step 1 and step 4.

[0010] An application of a diatomaceous earth-paraffin phase change material, characterized in that: a phase change coating is prepared with the diatomaceous earth-paraffin phase change material, a dispersion latex powder, a pigment filler powder and a functional additive are added in a certain proportion to prepare the diatomaceous earth-paraffin phase change material, a dispersion treatment is performed by a disperser, and after filtering, the coating is allowed to stand for 20 minutes to remove foam to obtain a phase change coating.

[0011] Preferably, in an application of a diatomaceous earth-paraffin phase change material, the functional additives include a defoaming agent, a dispersant sodium tripolyphosphate, a thickener hydroxyethyl cellulose and a defoaming agent.

[0012] Preferably, in an application of diatomaceous earth-paraffin phase change material, the dispersing machine operates at a speed of 1000 revolutions per minute and the operating duration is 15 minutes.

[0013] An application of diatomaceous earth-paraffin phase change material, using the diatomaceous earth-paraffin phase change material to prepare phase change heat storage mortar, adding sand and diatomaceous earth-paraffin phase change material into cement slurry in a certain proportion, using an instrument to automatically control stirring, to obtain diatomaceous earth-based phase change heat storage mortar.

[0014] Preferably, in an application of a diatomaceous earth-paraffin phase change material, the diatomaceous earth-paraffin phase change material is added in the last minute of stirring time.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The method of the present invention has reasonable design steps and is easy to operate. By modifying diatomaceous earth and paraffin, impurities and organic matter are prevented from blocking the pores, which is convenient for subsequent material preparation. By vacuum treatment and water bath heating, the phase change material can be effectively mixed and heated, and the corresponding stirring treatment is performed to ensure that the materials are evenly mixed and fully reacted, thereby ensuring the material preparation effect. 2. The diatomite-paraffin phase change material of the present invention can be applied to the preparation of phase change coatings, and has broad prospects for promotion and use. The amount of diatomite-paraffin phase change material added has a significant effect on the construction performance of the phase change coating, the surface drying time of the phase change coating, the alkali resistance of the phase change coating, and the washability of the phase change coating, and can meet different construction requirements; 3. The diatomaceous earth-paraffin phase change material in the present invention can be applied to the preparation of phase change heat storage mortar, and has broad prospects for promotion and use. The dosage of diatomaceous earth-paraffin phase change material has a significant effect on the fluidity, compressive strength and bonding strength of the phase change mortar, and can meet different construction requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the description of the specific implementation methods will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 It is a flowchart of the present invention; Figure 2 It is a schematic diagram of the construction properties of the phase change coating with different diatomaceous earth-paraffin phase change material dosages in the present invention; Figure 3 It is a schematic diagram of the surface drying time of the phase change coating with different diatomaceous earth-paraffin phase change material dosages in the present invention; Figure 4 It is a schematic diagram of the alkali resistance test of the phase change coating with different diatomaceous earth-paraffin phase change material dosages in the present invention; Figure 5 A schematic diagram of the number of times the phase change coating of the present invention can withstand washing with different diatomaceous earth-paraffin phase change material dosages; Figure 6 It is a schematic diagram of the fluidity of the phase change heat storage mortar with different diatomite-paraffin phase change material dosages in the present invention; Figure 7 It is a schematic diagram of the compressive strength of the phase change heat storage mortar with different diatomite-paraffin phase change material dosages in the present invention; Figure 8Schematic diagram of the bonding strength of the phase change heat storage mortar with different diatomaceous earth-paraffin phase change material dosages in the present invention. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] See also Figure 1-8 As shown, this embodiment is a preparation method of a diatomaceous earth-paraffin phase change material and its application. The preparation method of the diatomaceous earth-paraffin phase change material comprises the following steps: S1, diatomite modification treatment, Calcination treatment: Place the original diatomite in a high-temperature box-type electric furnace and calcine at 450°C for 2 hours; Acid washing: Weigh a certain amount of calcined modified diatomite, immerse it in a 5 mol / L hydrochloric acid solution at a liquid-to-solid ratio of 4:1, and then heat it in a water bath at 50°C for 4 hours while stirring. After completion, wash, filter and dry it; S2, paraffin modification treatment, The long-chain paraffin molecules are broken into shorter chains through cracking reactions. De-oiled refined wax is usually used as the raw material. This wax has a higher purity and a lower impurity content, which is conducive to the cracking reaction. Under a specific temperature and pressure, the reaction is carried out in a tubular cracking furnace to generate α-olefins of different chain lengths. These olefins can be further separated and purified to obtain products with different carbon numbers, thereby obtaining modified paraffin. S3, mixed vacuum treatment, Mixing and vacuuming: Weigh a certain proportion of modified diatomaceous earth and modified paraffin, mix them and put them into a suction filtration bottle, connect a circulating water vacuum pump, and evacuate to a certain vacuum degree; S4, water bath heating treatment, Heating and mixing: Place the filtration bottle in a water bath at 75°C for 2 hours, stirring during the process; S5, cooling and drying treatment, The diatomaceous earth fully adsorbed with the paraffin was taken out, cooled to room temperature and then placed for 24 hours to dry, thereby obtaining a diatomaceous earth-paraffin phase change material.

[0020] The invention discloses an application of a diatomaceous earth-paraffin phase change material. The diatomaceous earth-paraffin phase change material is used to prepare a phase change coating. A certain proportion of the diatomaceous earth-paraffin phase change material is added to prepare a dispersed latex powder, a pigment filler powder and a functional additive. The dispersion is carried out by a disperser. After filtering, the coating is allowed to stand for 20 minutes to remove foam, thereby obtaining a phase change coating.

[0021] The functional auxiliary agent comprises a defoaming agent, a dispersant sodium tripolyphosphate, a thickener hydroxyethyl cellulose and a defoaming agent.

[0022] The dispersing machine operates at a speed of 1000 revolutions per minute and lasts for 15 minutes.

[0023] An application of diatomaceous earth-paraffin phase change material, using the diatomaceous earth-paraffin phase change material to prepare phase change heat storage mortar, adding sand and diatomaceous earth-paraffin phase change material into cement slurry in a certain proportion, using an instrument to automatically control stirring, to obtain diatomaceous earth-based phase change heat storage mortar.

[0024] The diatomaceous earth-paraffin phase change material is added in the last minute of the stirring time.

[0025] During the water bath heating step of the diatomite modification treatment and the mixed vacuum treatment, stirring treatment should be performed to ensure that the materials are evenly mixed and fully reacted.

[0026] When preparing phase change coatings, ensure that all materials are added in the correct proportions and strictly control the speed and working time of the disperser to obtain phase change coatings with stable quality.

[0027] When preparing phase change heat storage mortar, the addition time of diatomaceous earth-paraffin phase change material should be strictly controlled to ensure its uniform distribution in the mortar.

[0028] In actual application, the dosage of diatomaceous earth-paraffin phase change material has the following effects on the construction performance of phase change coating, the surface drying time of phase change coating, the alkali resistance of phase change coating and the washability of phase change coating: 1. Pass Figure 2 The surface state of the phase change coatings with different diatomite-paraffin phase change material dosages applied on the cement board can be observed. No obvious protrusions and oily droplets were found in the phase change coating samples with different dosages. Among them: Sample a with a doping rate of 35% has the smoothest surface, the whitest color, and no small pores after film formation; The sample b with a doping content of 45% is yellower than a, and a small number of small pores can be observed on the surface; Sample c with a doping content of 55% has the yellowest surface color, the worst surface smoothness, and more pores; It can be concluded that the amount of diatomaceous earth-paraffin phase change material affects the adhesion and film-forming process of the coating, and thus affects the workability of the phase change coating. The increase of diatomaceous earth-paraffin phase change material makes the coating easier to operate, shortens the application time, and increases the difficulty of construction. 2. Pass Figure 3 It can be observed that A-1 with the least amount of diatomaceous earth-paraffin phase change material takes the longest time to reach the surface dry state. As the amount of diatomaceous earth-paraffin phase change material increases, the time required for the paint to reach the surface dry state becomes shorter. This is because the porous material diatomaceous earth contained in the diatomaceous earth-paraffin phase change material will absorb a certain amount of water, thereby shortening the drying time of the paint. The longest drying time of A-1 is 25 minutes and 15 seconds, and the shortest drying time of A-3 is 18 minutes and 23 seconds. Although there are certain differences in the surface drying time of the three groups of samples, they all meet the requirement that the surface drying time of the paint is less than 2 hours, which is convenient for construction; 3. In order to study the alkali resistance of phase change coatings, 2 / 3 of the length of the asbestos-free fiber cement board coated with phase change coatings was immersed in a saturated solution of calcium hydroxide. After immersion for 48 hours, the surface state of the coating was as follows: Figure 4 As shown, sample a has the least amount of admixture, its surface is flat, and no cracks or small bubbles are generated, while sample b has a surface full of small cracks, which is damaged by the alkaline solution. Sample c is a phase change coating with an admixture of 55%, and its surface has obvious bubbles and small pieces falling off, and its alkali resistance is very poor. The results show that the amount of diatomaceous earth-paraffin phase change material has a significant effect on the alkali resistance of phase change coatings, and the phase change coating with a small amount of diatomaceous earth-paraffin phase change material has better alkali resistance; 4. The number of times the coating can withstand washing is defined as the number of times the prepared phase change coating is applied to a non-asbestos fiber cement board of specified size and washed under specified conditions until the substrate is exposed at 100 mm in the middle of the test board. Figure 5 It can be seen that as the amount of diatomaceous earth-paraffin phase change material increases, the washability of the coating becomes worse, because the addition of diatomaceous earth-paraffin phase change material reduces the overall strength and uniformity of the coating, resulting in a decrease in the number of washability times.

[0029] In actual application, the dosage of diatomite-paraffin phase change material has the following effects on the fluidity, compressive strength and bonding strength of phase change mortar: 1. Since diatomite has strong water absorption, the addition of diatomite-paraffin phase change material will have a certain impact on the fluidity of mortar. Figure 6As shown in the figure, when the water reducing agent dosage is fixed at 3‰, the fluidity of the phase change mortar will deteriorate with the increase of the diatomite-paraffin phase change material dosage. When the diatomite-paraffin phase change material dosage is 0% and 5%, the fluidity of the phase change mortar is too large and the formed mortar shows obvious bleeding, and the forming is poor. The fluidity is 310mm and 300mm respectively. Compared with the blank group, when the diatomite-paraffin phase change material dosage in the phase change mortar exceeds 5%, the phase change mortar is easy to form and no bleeding occurs, because the porous diatomite material has strong water absorption. When the water reducing agent dosage is constant, the fluidity of the phase change mortar deteriorates with the increase of the D / PCM dosage in the phase change mortar. 2. Since diatomite is a porous material, the diatomite-paraffin phase change material after the paraffin is adsorbed replaces part of the sand and is added to the cement paste. The strength of the prepared phase change mortar matrix will be significantly reduced. Figure 7 As shown in the figure, with the increase of the dosage of diatomite-paraffin phase change material, the strength of phase change mortar decreases accordingly. When the dosage of diatomite-paraffin phase change material is 10%, the compressive strength of the composite phase change mortar decreases significantly (46.9%), and the 7d strength decreases by 24.6MPa. When the dosage is 25%, the 7d strength decreases to 13.8MPa, which is 73.7% lower than that of the blank control group. The 28d strength decreases to 32.1MPa, which is 71% lower than that of the blank control group. The change law of 28d strength is the same as that of 7d compressive strength. When paraffin is added to mortar as a phase change material, it will affect the hydration process of cement and cause a decrease in strength. Diatomite porous material has a significant pore structure, and the diatomite-paraffin phase change material itself has no strength and cannot play a role in strengthening the skeleton. Therefore, using diatomite-paraffin phase change material to replace sand will significantly affect the strength of the phase change mortar matrix. 3. When used for interior wall plastering, the bonding performance of mortar is very important, such as Figure 8 As shown in the figure, the bond strength of mortar increases with the increase of the content of diatomite-paraffin phase change material. When the content is 25%, the highest bond strength is 0.257MPa, which shows that the content of D / PCM has little effect on the bond strength of cement mortar, but will increase the bond strength to a certain extent. Because diatomite is a porous material, its main component is SiO2, which has a certain volcanic ash activity and can react with cement to generate cementitious substances, thereby improving the bond strength of cement mortar.

[0030] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0031] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a diatomaceous earth-paraffin phase change material, characterized in that: The following steps are involved: S1, diatomite modification treatment, a. Place the original diatomite in a high-temperature box-type electric furnace for calcination. b. Weigh a certain amount of calcined modified diatomite and inject it into a container, and immerse it in a hydrochloric acid solution at a liquid-to-solid ratio of 4:

1. c. Heat the container in a water bath at 50°C for 4 hours. d. Washing, filtering and drying the diatomaceous earth after acid washing; S2, paraffin modification treatment, a. Break long-chain paraffin molecules into shorter chains through cleavage reactions. b. further separating and purifying the pyrolysis products to obtain modified paraffin; S3, mixed vacuum treatment, Weigh a certain proportion of modified diatomaceous earth and modified paraffin, mix them and put them into a suction flask, connect it to a circulating water vacuum pump, turn on the switch and pump the suction flask to a certain vacuum degree; S4, water bath heating treatment, Heat the filtration bottle in a water bath at 75°C for 2 hours; S5, cooling and drying treatment, The diatomaceous earth fully adsorbed with paraffin was taken out, cooled to room temperature, and placed for 24 hours to dry, thereby obtaining a diatomaceous earth-paraffin phase change material.

2. The method for preparing a diatomaceous earth-paraffin phase change material according to claim 1, characterized in that: In step 1, the calcination temperature of the high-temperature box-type electric furnace is 450° C. and the calcination time lasts for 2 hours.

3. The method for preparing a diatomaceous earth-paraffin phase change material according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in step 1 is 5 mol / L.

4. The method for preparing a diatomaceous earth-paraffin phase change material according to claim 1, characterized in that: In step 2, deoiled refined wax is used as a raw material to carry out a cracking reaction in a tubular cracking furnace.

5. The method for preparing a diatomaceous earth-paraffin phase change material according to claim 1, characterized in that: In both step 1 and step 4, stirring is performed during water bath heating.

6. An application of diatomaceous earth-paraffin phase change material, characterized in that: The phase change coating is prepared with diatomaceous earth-paraffin phase change material, and diatomaceous earth-paraffin phase change material, dispersed latex powder, pigment filler powder and functional additives are added in a certain proportion, dispersed by a disperser, filtered and the coating is allowed to stand for 20 minutes to remove foam to obtain a phase change coating.

7. The use of a diatomaceous earth-paraffin phase change material according to claim 6, characterized in that: The functional auxiliary agent comprises a defoaming agent, a dispersant sodium tripolyphosphate, a thickener hydroxyethyl cellulose and a defoaming agent.

8. The use of a diatomaceous earth-paraffin phase change material according to claim 6, characterized in that: The dispersing machine operates at a speed of 1000 revolutions per minute and lasts for 15 minutes.

9. An application of a diatomaceous earth-paraffin phase change material, characterized in that: Diatomaceous earth-paraffin phase change material is used to prepare phase change heat storage mortar. Sand and diatomaceous earth-paraffin phase change material are added to cement slurry in a certain proportion, and stirring is automatically controlled by an instrument to obtain diatomaceous earth-based phase change heat storage mortar.

10. The use of a diatomaceous earth-paraffin phase change material according to claim 9, characterized in that: The diatomaceous earth-paraffin phase change material is added in the last minute of stirring time.

Citation Information

Patent Citations

  • Preparation method of diatomite and paraffin composite phase change material

    CN104194732A

  • Preparation method for stearic acid / modified diatomite composite phase-change energy storage material

    CN106883825A

  • Preparation method of modified diatomite-based porous phase change material

    CN113717696A